Diastasis of the Symphysis Pubis: Analysis of Three Cases - Güzel, Ali İrfan (Gynecology Obstetrics & Reproductive Medicine, 2012)
Diastasis of the symphisis pubis is the separation of normally joined pubic bones. This anomaly following vaginal delivery has a very low incidence. The most common symptom is pelvic pain and discomfort in the pubic region. The patients may also complain of pain with walking. In current study we aimed to report the clinical features of three patients diagnosed as diastasis of the symphisis pubis delivered at our clinic. All women admitted to the clinic with severe pelvic pain with walking.